2011 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC) 2011
DOI: 10.1109/vlhcc.2011.6070387
|View full text |Cite
|
Sign up to set email alerts
|

Modeling programmer navigation: A head-to-head empirical evaluation of predictive models

Abstract: Software developers frequently need to perform code maintenance tasks, but doing so requires time-consuming navigation through code. A variety of tools are aimed at easing this navigation by using models to identify places in the code that a developer might want to visit, and then providing shortcuts so that the developer can quickly navigate to those locations. To date, however, only a few of these models have been compared head-to-head to assess their predictive accuracy. In particular, we do not know which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
4
33
1
Order By: Relevance
“…Our results on switches to methods in close proximity further support the findings of a recent head-to-head study that compared different models of a programmer's navigation [29] and that suggested to use models to approximate a developer's navigation based on the spatial proximity of methods within the source code.…”
Section: Interaction Contextsupporting
confidence: 86%
See 4 more Smart Citations
“…Our results on switches to methods in close proximity further support the findings of a recent head-to-head study that compared different models of a programmer's navigation [29] and that suggested to use models to approximate a developer's navigation based on the spatial proximity of methods within the source code.…”
Section: Interaction Contextsupporting
confidence: 86%
“…Based on such automatically captured interaction histories-logs of the code elements a developer interacted with along with a timestamp-researchers have, for instance, investigated how developers work in an IDE [27], how they navigate through code [28,29,47], or how developers' micro interaction patterns might be used for defect prediction [24]. Even the Eclipse team themselves undertook a major data collection project called the Usage Data Collector that, at its peak, collected data from thousands of developers using Eclipse.…”
Section: User Interaction Monitoringmentioning
confidence: 99%
See 3 more Smart Citations